Simulation modeling of ground movement of arriving and departing aircraft at Changi Airport - Yee, Shuen Hwee (2018)
Taxi delay can be used as a performance indicator at airports. With increased demand for air travel, airports would face increased congestion as the capacity becomes a bottleneck. This delay would be amplified in the event of a disruptions such as runway closure. A runway can be closed due to weather conditions or accidents. In order to effectively manage disruption operations at an airport, a simulation model can be used as a planning tool. This final year project aims to use AirTOp as a simulation software to study the effects of a disruption to airport operations and to minimize the consequent delay. The author will develop a model of Changi Airport that would allow the author to obtain new flight sequences and gate allocation. By collecting and comparing delay results under normal airport operations and disruption condition, effective gate allocation strategies and flight sequencing strategies can be obtained. Smaller parking position groups are assigned to individual flight plans instead of assigning the entire terminal to better prevent gate conflicts from occurring. Furthermore, when no more than 5 aircrafts are allowed to pushback simultaneously, the taxi delay is also successfully reduced. Thus, the new flight sequence obtained in a post-disruption context will result in less flight delay compared to the prior arrangement where flights are scheduled to leave whenever the runway is available for queueing.